Information resources availability, utilisation and job performance of academic librarians in selected university libraries in North-Central Nigeria (2020)
This study examined the level of information resources availability, utilisation and job performance in selected university libraries in North-Central Nigeria. Four research questions and three hypotheses were tested at 0.05 level of significance. Task-Technology Fit was the theoretical framework underpinning the study. The study population consisted of 128 academic librarians in seven university libraries. Out of this total, 103 copies were duly completed and returned for quantitative analysis, giving a response rate of 81%. Sampling was purposive and enumerative as all members of the population were used for the study. Data collected were analysed using SPSS. Findings indicated that 90% of the respondents noted that there is high availability of information resources for their job performance while 77(75%) of the respondents revealed that there is high utilisation of e- resources. A relationship between level of information resources utilisation and academic librarians job performance was established in the selected university libraries at (β= 0.591; p<0.05). The hypotheses tested revealed that job performance was significantly related to information utilisation. Though, information availability was found to be positively related to job performance, the relationship was not statistically significant (β= 0.081; p>0.05). Theoretically, the study contributed to validating Task-Technology Fit Theory. Based on these findings, some recommendations were made.